AB0744 Developing Thai Siriraj Psoriatic Arthritis Screening Tool and Validated Thai Psoriasis Epidemiology Screening Tool and The Early Arthritis for Psoriatic Patients. (15th July 2016) - Chiowchanwisawakit, P.; Wattanamongkolsil, L.; Srinonprasert, V.; Petcharat, C.; Katchamart, W.
Abstract : Background: Majority of PsA patients present with Ps before onset of arthritis up to 10 years. Ps patients are generally taken care by general practitioners or dermatologists therefore they play a key role for early detection of PsA. There are a few screening tools available; however, it has been reported that they have a wide range of sensitivity and specificity around 24- 90% and 40–94%, respectively, in the different studies 1 . There is no screening tool which has been verified in Thai content. Furthermore, it would be essential to have a simple tool with good discriminating property. Objectives: To validate Thai version of the Psoriasis Epidemiology Screening Tool (PEST) 2 and the Early ARthritis for Psoriatic patients' questionnaire (EARP) 3, and to develop the new tool for screening psoriatic arthritis (PsA) among psoriasis (Ps) patients. Methods: This was a cross-sectional study. Ps patients visiting psoriasis clinic at Siriraj Hospital were recruited. They filled out EARP, and PEST, and were evaluated full musculoskeletal history, examination and radiography. Diagnosis of PsA was based on a rheumatologist's evaluation and fulfilled C lAS sification criteria for P soriatic Ar thritis. Receiver operator characteristic (ROC) curves, sensitivity, and specificity were used to determine the performance of tools. Siriraj Psoriatic Arthritis screening Tool (SiPAT) was composed from the most relevant questions regarding peripheral arthritis, axial inflammation, enthesitis selected from multivariate analysis. Results: A total of 159 patients, prevalence of PsA was 78.6%. The ROC curve analyses of the Thai EARP, PEST, and SiPAT were 0.90 (95%CI: 0.84, 0.96), 0.85 (0.78, 0.92), and 0.89 (0.83, 0.95), respectively. The sensitivities of SiPAT, Thai EARP and PEST were 91.0, 83.0, and 72.0%, respectively while the specificities were 69.0, 79.3, and 89.7%, respectively. Conclusions: Thai EARP and SiPAT have diagnostic performance better than Thai PEST. SiPAT could be proposed as a simple and effective tool for screening PsA among Ps patients. References: Haroon M, Kirby B, FitzGerald O. High prevalence of psoriatic arthritis in patients with severe psoriasis with suboptimal performance of screening questionnaires. Ann Rheum Dis. 2013;72(5):736–40. Ibrahim GH, Buch MH, Lawson C, Waxman R, Helliwell PS. Evaluation of an existing screening tool for psoriatic arthritis in people with psoriasis and the development of a new instrument: the Psoriasis Epidemiology Screening Tool (PEST) questionnaire. Clin Exp Rheumatol. 2009;27(3):469–74. Tinazzi I, Adami S, Zanolin EM, Caimmi C, Confente S, Girolomoni G, et al. The early psoriatic arthritis screening questionnaire: a simple and fast method for the identification of arthritis in patients with psoriasis. Rheumatology (Oxford). 2012;51:2058–63. Acknowledgement: This study is supported by investigator- initiated research grant from Pfizer. Disclosure of Interest: P. Chiowchanwisawakit Grant/research support from: investigator- initiated research grant from Pfizer., L. Wattanamongkolsil: None declared, V. Srinonprasert: None declared, C. Petcharat: None declared, W. Katchamart: None declared